LECTURERS’ PERCEPTIONS OF ETHICAL ISSUES RELATED TO THE INTEGRATION OF AI TOOLS INTO WRITING ACTIVITIES: A MULTIPLE CASE STUDY - Annisa Astrid; Deta Desvitasari; Muhamad Chalik Chairuman; M. Raditya Ramadhani Dirgantara; Fatimah Azzahra (Language and Education Journal, 2025)
This study explores English writing lecturers' perspectives on ethical concerns related to the incorporation of Artificial Intelligence (AI) tools in writing activities for English Department students. A qualitative multiple-case study approach was utilized. The instrument used was semi-structured interviews. The subjects of the study were 12 academics from four colleges with differing accreditation levels who were drawn using purposive sampling. Thematic analysis identified six principal ethical concerns: (1) The imperative to have an ethical attitude; 2) The concerns about privacy and data security threats; 3) The emergence of potential gaps among students; 4) The degradation of academic integrity; 5) The obligation of academic responsibility; and 6) The need for regulations and guidelines for AI use. Lecturers typically endorse AI integration to facilitate idea development and pre-writing tasks; however, they emphasize the necessity of restricting its use to maintain originality, critical thinking, and student accountability. The results underscore the pressing necessity for explicit institutional policies, ethical AI literacy, equitable access, and strategies that reconcile technology advantages with the development of autonomous writing skills. This research provides insights for the development of AI-enhanced writing education that conforms to ethical, pedagogical, and institutional concerns.